Detection of Klebsiella pneumonia DNA and ESBL positive strains by PCR-based CRISPR-LbCas12a system - Wang, Shang; Wang, Shan; Tang, Ying; Peng, Guoyu; Hao, Tongyu; Wu, Xincheng; Wei, Jiehong; Qiu, Xinying; Zhou, Dewang; Zhu, Shimao; Li, Yuqing; Wu, Song (Frontiers in Microbiology, 2023)
Introduction Klebsiella pneumonia (K. pneumonia) is a Gram-negative bacterium that opportunistically causes nosocomial infections in the lung, bloodstream, and urinary tract. Extended-spectrum β-Lactamases (ESBLs)-expressed K. pneumonia strains are widely reported to cause antibiotic resistance and therapy failure. Therefore, early identification of K. pneumonia, especially ESBL-positive strains, is essential in preventing severe infections. However, clinical detection of K. pneumonia requires a time-consuming process in agar disk diffusion. Nucleic acid detection, like qPCR, is precise but requires expensive equipment. Recent research reveals that collateral cleavage activity of CRISPR-LbCas12a has been applied in nucleic acid detection, and the unique testing model can accommodate various testing models. Methods This study established a system that combined PCR with CRISPR-LbCas12a targeting the K. pneumoniae system. Additionally, this study summarized the antibiotic-resistant information of the past five years’ K. pneumoniae clinic cases in Luohu Hospital and found that the ESBL-positive strains were growing. This study then designs a crRNA that targets SHV to detect ESBL-resistant K. pneumoniae. This work is to detect K. pneumoniae and ESBL-positive strains’ nucleic acid using CRISPR-Cas12 technology. We compared PCR-LbCas12 workflow with PCR and qPCR techniques. Results and Discussion This system showed excellent detection specificity and sensitivity in both bench work and clinical samples. Due to its advantages, its application can meet different detection requirements in health centers where qPCR is not accessible. The antibiotic-resistant information is valuable for further research.